Genetic studies of coliphage P1. III. Extended genetic map. - Walker, D H (1976)
An extensive genetic map of coliphage P1 has been constructed for 113 amber mutants, using primarily a modification of the conventional complementation spot test. These spot tests failed to classify the mutants into cistrons, but when they were quantitated they permitted assignment of the mutants into 10 linkage clusters. Furthermore, a linear order could be deduced for most of the mutants within each cluster. This strongly suggested that recombination was the predominant event generating plaques and that, for the practical purpose of rapid genetic mapping, such spot tests could be considered as a series of two-factor crosses. Six of the 10 linkage clusters correlated with the P1 genetic map established by Scott (1968). The locations of the remaining four clusters were determined by three-factor crosses and by prophage deletion mapping. The nonrandom occurrence of termini for 14 deletion prophages, which we established previously (Walker and Walker, 1975), and the coincidence of these termini with five out of ten regions demarcating the linkage clusters are discussed. Complementation tests in liquid frequently gave ambiguous results. Therefore, cistron designations were not assigned.